Changes in gene expression in PBMCs profiles of PPAR alpha target genes in obese and non-obese individuals during fasting - Felicidade, Ingrid [UNESP]; Marcarini, Juliana Cristina [UNESP]; Carreira, Clisia Mara; Amarante, Marla Karine; Afrnan, Lydia A.; Mantoyani, Mario Sergio; Ribeiro, Lucia Regina [UNESP] (Karger, 2015)
Background: The prevalence of obesity has risen dramatically and the World Health Organization estimates that 700 million people will be obese worldwide by 2015. Approximately, 50% of the Brazilian population above 20 years of age is overweight, and 16% is obese. Aim: This study aimed to evaluate the differences in the expression of PPAR alpha target genes in human peripheral blood mononuclear cells (PBMCs) and free fatty acids (FFA) in obese and non-obese individuals after 24 h of fasting. We first presented evidence that Brazilian people exhibit expression changes in PPARa target genes in PBMCs under fasting conditions. Methods: Q-PCR was utilized to assess the mRNA expression levels of target genes. Results: In both groups, the FFA concentrations in. creased significantly after 24 h of fasting. The basal FFA mean concentration was two-fold higher in the obese group compared with the non-obese group. After fasting, all genes evaluated in this study showed increased expression levels compared with basal expression in both groups. Conclusion: However, our results reveal no differences in gene expression between the obese and non-obese, more studies are necessary to precisely delineate the associated mechanisms, particularly those that include groups with different degrees of obesity and patients with diabetes mellitus type 2 because the expression of the main genes that are involved in beta-oxidation and glucose level maintenance are affected by these factors.
Keywords: Free fatty acids; Obesity; PBMC; PPAR alpha